Reversible C=C Bond Activation by an Intramolecularly Coordinated Antimony(I) Compound. Issue 56 (28th August 2019) - Kořenková, Monika; Hejda, Martin; Erben, Milan; Jirásko, Robert; Jambor, Roman; Růžička, Aleš; Rychagova, Elena; Ketkov, Sergey; Dostál, Libor
Abstract: Invited for the cover of this issue is the group of Libor Dostál at the University of Pardubice, Czech Republic, and colleagues at the G. A. Razuvaev Institute of Organometallic Chemistry, Nizhny Novgorod, Russia. The image depicts an amusement park designed around the antimony compounds reported in this paper. Read the full text of the article at10.1002/chem.201902968 . Abstract : " The reported activation of quite inert C=C double bonds by an easily available low‐valent Group 15 compound can be seen as a significant breakthrough in the area of main group element chemistry " Read more about the story behind the cover in the Cover Profile and about the research itself on page 12884 ff. (DOI:10.1002/chem.201902968 ).